Polymer based MWCNT/Nickel Zinc Ferritenanocomposites for RAS application with simulation. (2019) - Siva Nagasree, P.; Ramji, Dr.K.; Haritha, T.; Santoshi, B.V.S.R.N.
Abstract: The X-band microwave characterization of epoxy based MWCNTs/Nickel Zinc Ferrite composite for RAS was presented.Varying MWCNT weight percentage and fixing Nickel Zinc Ferrite five different composites were fabricated by in situ polymerization process. By means of S parameters given by VNA, the real and the imaginary parts of the relative complex permittivity and relative complex permeability were obtained. The values of reflection loss for four layered RAS with different wt percentages of fillers were determined by simulation using MATLAB code . A four layered RAS at central frequency of 12 Ghz shown the max reflection loss of -31 db and -15 db corresponding to 95 % absorption for band width of 1Ghz.